Combined Molecular and Biochemical Approach Identifies Aspergillus japonicus and Aspergillus aculeatus as Two Species - Pařenicová, Lucie (American Society for Microbiology, 2001)
We examined nine Aspergillus japonicus isolates and 10 Aspergillus aculeatus isolates by using molecular and biochemical markers, including DNA sequences of the ITS1-5.8S rRNA gene-ITS2 region, restriction fragment length polymorphisms (RFLP), and secondary-metabolite profiles. The DNA sequence of the internal transcribed spacers (ITS1 and ITS2) and the 5.8S rRNA gene could not be used to distinguish between A. japonicus and A. aculeatus but did show that these two taxa are more closely related to each other than to other species of black aspergilli. Aspergillus niger pyruvate kinase (pkiA) and pectin lyase A (pelA) and Agaricus bisporus 28S rRNA genes, which were used as probes in the RFLP analysis, revealed clear polymorphism between these two taxa. The A. niger pkiA and pelA probes placed six strains in an A. japonicus group and 12 isolates in an A. aculeatus group, which exhibited intraspecific variation when they were probed with the pelA gene. The secondary-metabolite profiles supported division of the isolates into the two species and differed from those of other black aspergilli. The strains classified as A. japonicus produced indole alkaloids and a polar metabolite, while the A. aculeatus isolates produced neoxaline, okaramins, paraherquamidelike compounds, and secalonic acid. A. aculeatus CBS 114.80 showed specific RFLP patterns for all loci examined. The secondary-metabolite profile of strain CBS 114.80 also differed from those of A. japonicus and A. aculeatus. Therefore, this strain probably represents a third taxon. This study provides unambiguous criteria for establishing the taxonomic positions of isolates of black aspergilli, which are important in relation to industrial use and legal protection of these organisms.